Choledochoplasty by Vein Grafts in Iatrogenic Bile Duct Injuries. Issue 3 (1992) - Salim, Aws S.
Abstract : The quality of immediate repair of common bile duct injuries with or without tissue loss occurring during elective cholecystectomy is crucial and maybe the sole factor behind future stricture formation with its considerable morbidity and mortality. Successful repair of iatrogenic common bile duct injuries has been achieved by immediate saphenous vein grafts in two patients with cystic duct avulsion, in one patient whose duct was split by a balloon catheter, and in one patient where a segment of the duct was resected. Follow-up for 5 years demonstrated that the grafting remained sound and produced no complications. Consequently, the immediate repair of iatrogenic bile duct injuries using vein grafts deserves consideration.